SINUS HISTIOCYTOSIS WITH MASSIVE LYMPHADENOPATHY (ROSAI-DORFMAN DISEASE) - CYTOMORPHOLOGIC ANALYSIS ON FINE-NEEDLE ASPIRATES - Schmitt, F. C. (Wiley-Blackwell, 1992)
Cytomorphologic characteristics of smears from fine-needle aspirates (FNA) of three cases of sinus histiocytosis with massive lymphadenopathy (SHML) (Rosai-Dorfman disease) are described. All aspirates showed mature lymphocytes, plasma cells, and large pale histiocytes with well-preserved lymphocytes within the cytoplasm (lymphocytophagocytosis). The cases were confirmed by surgical biopsy, and the immunohistochemical findings suggested a macrophage origin for this lesion. The value of FNA analysis as an aid to diagnosis of SHML is discussed.
Keywords: SHML; LYMPH NODE DISEASE; FINE-NEEDLE ASPIRATION